Liver injury is independently associated with adverse clinical outcomes in patients with COVID-19 - Yip, Terry Cheuk-Fung; Lui, Grace Chung-Yan; Wong, Vincent Wai-Sun; Chow, Viola Chi-Ying; Ho, Tracy Hang-Yee; Li, Timothy Chun-Man; Tse, Yee-Kit; Hui, David Shu-Cheong; Chan, Henry Lik-Yuen; Wong, Grace Lai-Hung (Gut, 2021)
ObjectiveData on serial liver biochemistries of patients infected by different human coronaviruses (HCoVs) are lacking. The impact of liver injury on adverse clinical outcomes in coronavirus disease 2019 (COVID-19) patients remains unclear.DesignThis was a retrospective cohort study using data from a territory-wide database in Hong Kong. COVID-19, severe acute respiratory syndrome (SARS) and other HCoV patients were identified by diagnosis codes and/or virological results. Alanine aminotransferase (ALT)/aspartate aminotransferase (AST) elevation was defined as ALT/AST ≥2 × upper limit of normal (ie, 80 U/L). The primary end point was a composite of intensive care unit (ICU) admission, use of invasive mechanical ventilation and/or death.ResultsWe identified 1040 COVID-19 patients (mean age 38 years, 54% men), 1670 SARS patients (mean age 44 years, 44% men) and 675 other HCoV patients (mean age 20 years, 57% men). ALT/AST elevation occurred in 50.3% SARS patients, 22.5% COVID-19 patients and 36.0% other HCoV patients. For COVID-19 patients, 53 (5.1%) were admitted to ICU, 22 (2.1%) received invasive mechanical ventilation and 4 (0.4%) died. ALT/AST elevation was independently associated with primary end point (adjusted OR (aOR) 7.92, 95% CI 4.14 to 15.14, p<0.001) after adjusted for albumin, diabetes and hypertension. Use of lopinavir–ritonavir ±ribavirin + interferon beta (aOR 1.94, 95% CI 1.20 to 3.13, p=0.006) and corticosteroids (aOR 3.92, 95% CI 2.14 to 7.16, p<0.001) was independently associated with ALT/AST elevation.ConclusionALT/AST elevation was common and independently associated with adverse clinical outcomes in COVID-19 patients. Use of lopinavir–ritonavir, with or without ribavirin, interferon beta and/or corticosteroids was independently associated with ALT/AST elevation.